Isolation and Characterization of Microsatellite Markers Useful for Exploring Introgression Among Species in the Diverse New Zealand Cicada Genus Kikihia. Issue 1 (5th April 2015) - Wade, Elizabeth J.; Simon, Chris
Abstract : The New Zealand cicada genus Kikihia Dugdale 1971 exhibits more than 20 contact zones between species pairs that vary widely in their divergence times (between 20, 000 and 2 million years) in which some level of hybridization is evident. Mitochondrial phylogenies suggest some movement of genes across species boundaries. Biparentally inherited and quickly evolving molecular markers like microsatellites are useful for assessing gene flow levels. Here, we present six polymorphic microsatellite loci that amplify DNA from seven species across the genus Kikihia ; Kikihia "northwestlandica, " Kikihia "southwestlandica, " Kikihia muta, Kikihia angusta, Kikihia "tuta, " Kikihia "nelsonensis, " and Kikihia "murihikua." The markers were developed using whole-genome shotgun sequencing on the 454 pyrosequencing platform. Moderate to high levels of polymorphisms were observed with 14–47 alleles for 213 individuals from 15 populations. Observed and expected heterozygosity range from 0 to 1 and 0.129 to 0.945, respectively. These new markers will be instrumental for the assessment of gene flow across multiple contact zones in Kikihia.